Comparative Analysis of Network Quality Using QOS Parameters on Mikrotik Routers Using the Queue Tree and Simple Queue Methods - Anni Zulfia; Dahlan Abdullah; Fajriana Fajriana (Malikussaleh University, Aceh, Indonesia, 2023)
The research was conducted by researchers at Trienggadeng State Vocational School located on Jl Banda Aceh-Medan KM 152, Kec. Trienggadeng Regency. Pidie Jaya. This research is based on the importance of the network in the ongoing teaching and learning process in the network and computer labs, the network in the lab is currently not managed properly and the distribution of bandwidth is not evenly distributed. To get a good internet connection, it is necessary to distribute bandwidth evenly, which can be done using a proxy router. One of the features for distributing bandwidth evenly in the proxy router can be applied using the simple queue and queue tree methods, knowing network quality can be done using Quality of Service (QoS) measurements. This study aims to determine the analysis of network quality using Qos on proxy routers using the simple queue and queue tree methods. The method used in this study is to use the action research method (action research), the stages of the research are analyzing, data collection, data completeness, making network designs, and taking action. The results obtained for network analysis in a comparative study between simple queue and queue tree networks, the results for the delay obtained by the queue tree are 9 ms, packet loss = 0%, and throughput = 549 k. Whereas the simple queue obtains the value from the QoS measurement by performing calculations with the equation formula to obtain a value of delay = 8 ms, packet loss = 0.15% and throughput = 629 k. Based on the Tiphon standard, it can be concluded that for delay, a queue tree is better with a value above the simple queue with a very good index, the packet loss queue tree is better than the simple queue, the index is very good, the throughput of the simple queue is better compared to the throughput queue tree. This research shows that overall Queue Tree is more optimal for QoS.